2017
DOI: 10.1002/2017jf004293
|View full text |Cite
|
Sign up to set email alerts
|

Morphodynamic modeling of a large inside sandbar and its dextral morphology in a convergent estuary: Qiantang Estuary, China

Abstract: We investigate the evolution of a large‐scale sand body, a unique type of sandbars in a convergent estuary. Specifically, we analyze and simulate the sand deposition system (defined as an inside bar) in the Qiantang Estuary (QE) in China. The deposit is 130 km long and up to 10 m thick and is characterized by a dextral morphology in the lower QE. Numerical simulation is carried out using an idealized horizontal 2‐D morphodynamic model mimicking the present QE settings. Our results indicate that the morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…However, tidal bars occur in natural systems (e.g., Western Scheldt) where the Coriolis force is a first-order term in the momentum balance. The importance of Coriolis on the hydro-morphodynamics in tidal channels is supported by several other studies, e.g., Valle-Levinson (2008), Winant (2008), Xie et al (2017), and Olabarrieta et al (2018). Furthermore, 2D morphological simulations similar (but now with and without the Coriolis effect) with those performed by Hibma et al (2004) show clear differences between the initial formation of bottom patterns with and without the Coriolis effect taken into account (see Fig.…”
Section: Introductionsupporting
confidence: 79%
“…However, tidal bars occur in natural systems (e.g., Western Scheldt) where the Coriolis force is a first-order term in the momentum balance. The importance of Coriolis on the hydro-morphodynamics in tidal channels is supported by several other studies, e.g., Valle-Levinson (2008), Winant (2008), Xie et al (2017), and Olabarrieta et al (2018). Furthermore, 2D morphological simulations similar (but now with and without the Coriolis effect) with those performed by Hibma et al (2004) show clear differences between the initial formation of bottom patterns with and without the Coriolis effect taken into account (see Fig.…”
Section: Introductionsupporting
confidence: 79%
“…4b). The serious bed degradation can be explained by the fact that the discharge during a river flood event is much larger than the normal discharge which is around 1000 m 3 /s (Chen et al, 2006;Xie et al, 2017a). In previous studies, the cross-sectional area and the cross-sectionally averaged depth, have been found as a power function of the river discharge (Leopold and Maddock, 1953;Smith, 1974;Han et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Based on sedimentological surveys, it has been revealed that the sediment of this large sedimentary system is from the adjacent Changjiang River (Chien et al, 1964;Chen et al, 1990;Zhang et al, 2015). Recent modeling by Xie et al (2017a) found that the deposits would grow unlimitedly under normal discharge condition due to the continuous sediment import by flood dominance, and the growth can be constrained by high discharge. Xie et al (2017b) also analyzed the morphological response of the Qiantang Estuary-Hangzhou Bay system to the reduction of sediment load from the adjacent Changjiang Estuary and the large-scale embankment within the estuary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution is relatively weak in the shallow coastal zone below 0 m, yet this is precisely where significant bathymetric change should be expected. These topobathymetric DEMs form an essential boundary condition for many hydrodynamic models, including hurricane storm surge (Hope et al, ; Xing et al, ), and flood and tidal modeling (Gaweesh & Meselhe, ; Vinh et al, ; Xie et al, ). While such models are validated to varying degrees, it is likely that modeling can be improved, particularly in very shallow regions, with improved DEMs.…”
Section: Potential Resilience Analysis Toolsmentioning
confidence: 99%